Can trained volunteers make a difference at mealtimes for older people in hospital? A qualitative study of the views and experience of nurses, patients, relatives and volunteers in the Southampton Mealtime Assistance Study. (12th August 2014) - Robison, Judy; Pilgrim, Anna L.; Rood, Gemma; Diaper, Norma; Elia, Marinos; Jackson, Alan A.; Cooper, Cyrus; Aihie Sayer, Avan; Robinson, Sian; Roberts, Helen C.
Abstract : Background: Malnutrition is common amongst hospitalised older patients and associated with increased morbidity and mortality. Poor dietary intake results from factors including acute illness and cognitive impairment but additionally patients may have difficulty managing at mealtimes. Use of volunteers to help at mealtimes is rarely evaluated. Objectives: To obtain multiple perspectives on nutritional care of older inpatients, acceptability of trained volunteers and identify important elements of their assistance. Design: A qualitative study 1 year before and after introduction of volunteer mealtime assistants on one ward and parallel comparison with a control ward in a Medicine for Older People department at a UK university hospital. Participants and methods: Semi‐structured interviews and focus groups, in baseline and intervention years, with purposively sampled nursing staff at different levels of seniority; patients or close relatives; and volunteers. Results: At baseline staff felt under pressure with insufficient people assisting at mealtimes. Introducing trained volunteers was perceived by staff and patients to improve quality of mealtime care by preparing patients for mealtimes, assisting patients who needed help, and releasing nursing time to assist dysphagic or drowsy patients. There was synergy with other initiatives, notably protected mealtimes. Interviews highlighted the perceived contribution of chronic poor appetite and changes in eating patterns to risk of malnutrition. Conclusions: Improved quality of mealtime care attributed to volunteers' input has potential to enhance staff morale and patients'/relatives' confidence. A volunteer mealtime assistance scheme may work best when introduced in context of other changes reflecting commitment to improving nutrition. Implications for practice: (i) A mealtime assistance scheme should incorporate training, supervision and support for volunteers; (ii) Good relationships and a sense of teamwork can develop between wards staff and volunteers; (iii) Impact may be maximised in the context of 'protected mealtimes'.